Applications of inertial measurement units (IMUs) in nordic skiing - Aminian, K. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
Considering current issues in complex instrumentation (e.g., treadmill, marker-based motion capture system and force sensors), which restricts the movement analysis in laboratory setting, a convenient solution for motion capture in field activity and snow sport is the use of body worn sensors. Wearable systems using inertial measurement units (accelerometers and gyroscopes) have been proposed in a variety of sport disciplines, but their application to skiing and particularly Nordic skiing is new.